PENYULUHAN PENANGANAN INFEKSI ANISAKIS SP PADA MASYARAKAT DI TEMPAT PENJUALAN IKAN (TP) DESAPA KOTA KUPANG - Almet, Julianty; Wuri, Diana Agustiani; Djungu, Dewi Fesbayati Lestari; Utami, Tri (Universitas Nusa Cendana, 2025)
Anisakiasis is a zoonotic disease caused by infection with the parasitic worm Anisakis sp. This parasite is commonly found in raw or undercooked marine fish that humans consume. The disease is transmitted when Anisakis larvae are ingested and attach to the human digestive tract wall. Clinical symptoms of anisakiasis include abdominal pain, nausea, vomiting, and sometimes severe allergic reactions such as anaphylaxis. Prevention of anisakiasis can be achieved by thoroughly cooking fish or freezing it before consumption. Awareness of this risk and education on proper fish preparation and cooking methods can reduce the incidence of the disease among vulnerable populations. Community outreach activities at TPI Oesapa, focusing on disease recognition and anisakiasis control, serve as a preventive measure by building public knowledge and providing education to the community. This approach helps mitigate the spread of the disease.